Analisis sitogenetik sel epitel mukosa bukal pekerja stasiun pengisi bahan bakar umum di kota Yogyakarta - Regina TC. Tandelilin; Elastria Widita; Rini Maya Puspita; Tang Sze Mun (Universitas Gadjah Mada, 2021)
Workers employed in petroleum station have a high-risk exposure to a wide range of toxic compounds with known mutagenic and carcinogenic potential. Cytogenetic damage might have happened if they continuously exposed to petroleum derivatives. This study aimed to analyse the cytogenetic damage in exfoliated buccal cells among petroleum station workers in Yogyakarta City. This cross-sectional study was carried out on 30 petrol station workers who are working at a different petrol station in Yogyakarta and the control group consisted of 30 healthy subjects. Examination for all subjects included frequencies of nuclear abnormalities, including pycnosis, karyorrhexis, and karyolysis. Cytological preparations were stained according to papanicolaou reaction and analyzed under light microscope for making a score for degenerative nuclear alterations (pycnosis, karyolysis and karyorrhexis). Analysis of buccal cells revealed that frequencies of pycnosis and karyorrhexis in petrol station workers were significantly higher than the control group (P<0.05). Conversely, there was no significant difference in karyolisis among groups. These findings indicate that the petrol station workers are under the risk of significant cytogenetic damage, particularly pycnosis and karyorrhexis.